Electrolyte and lithium ion battery

By using an electrolyte containing carbonate solvents, lithium salts, non-polar diluents and sulfur-based additives in lithium-ion batteries, the problem of oxidation and decomposition of the electrolyte in a high-charge state is solved, and the cycle life of the lithium-ion battery and the stability of the battery performance is achieved.

CN119581663AActive Publication Date: 2025-03-07AESC DYNAMICS TECHNOLOGY (ORDOS) LTD +2

Patent Information

Application Number
CN202411776112.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-07
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

In the high-charge state of existing lithium-ion batteries, the electrolyte undergoes oxidation and decomposition on the positive electrode surface, resulting in rapid capacity loss and gas generation, which in turn causes attenuation of the battery cycle life.

Method used

An electrolyte including a carbonate solvent, a lithium salt, a non-polar diluent and a sulfur-based additive is used to reduce the contact between the carbonate solvent and the positive electrode surface through a non-polar diluent, reduce the probability of oxidation and decomposition, and a dense SEI film is generated at the negative electrode through a sulfur-based additive, thereby preventing the reduction and decomposition of the non-polar diluent.

Benefits of technology

It significantly reduces the side reactions of the electrolyte on the positive electrode surface, extends the cycle life of the lithium-ion battery, and maintains the stability of other battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581663A_ABST
    Figure CN119581663A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of secondary batteries, in particular to a high-voltage-resistant lithium ion battery electrolyte. The electrolyte comprises a solvent, a lithium salt, a non-polar diluent and a chalcogenide additive represented by a formula (1), (2) or (3). Wherein the solvent comprises a carbonic ester solvent; the lithium salt is dissolved in the solvent; the mass fraction of the non-polar diluent in the electrolyte is 21%-60%; the mass ratio of the sulfur additive to the non-polar diluent is (1: 200)-(1: 10). The electrolyte provided by the invention can improve the cycle capability of the lithium ion battery and ensure that other performances of the lithium ion battery are kept stable. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of secondary batteries, in particular to an electrolyte and a lithium ion battery. Background Art

[0002] At present, lithium-ion batteries are developing rapidly in the fields of electric vehicles and large-scale energy storage, occupying a large market share. In order to pursue faster charging speeds and longer driving range of electric vehicles, lithium-ion batteries are required to have higher fast charging capabilities and higher energy density.

[0003] In the prior art, some positive electrode materials, such as high-nickel ternary positive electrodes, can significantly improve the energy density of lithium-ion batteries. However, due to the instability of highly active metal ions such as trivalent nickel ions, they will react with air to generate surface residual alkali. The surface residual alkali has a strong catalytic activity on the electrolyte, causing the electrolyte to undergo continuous oxidative decomposition on the surface of the positive electrode, resulting in rapid capacity loss and gas generation in the lithium-ion battery, causing the battery cycle life to decay. When the lithium-ion battery is in a high state of charge (SOC), the degree of oxidative decomposition or other side reactions of the electrolyte on the surface of the positive electrode will be more intense, causing the cycle life of the lithium-ion battery to decay more seriously. Summary of the invention

[0004] In view of the above problems, the present invention provides an electrolyte, which has a weaker side reaction on the positive electrode surface when the lithium-ion battery is in a high SOC state, thereby significantly improving the cycle life of the lithium-ion battery.

[0005] One aspect of the present invention provides an electrolyte, which includes a solvent, a lithium salt, a non-polar diluent and a sulfur-based additive. The solvent includes a carbonate solvent; the lithium salt is dissolved in the solvent; the mass fraction of the non-polar diluent in the electrolyte is 21%-60%; the mass ratio of the sulfur-based additive to the non-polar diluent is 1:200-1:10, and the sulfur-based additive is a compound represented by formula (1), formula (2) or formula (3).

[0006]

[0007] Optionally, the non-polar diluent is one or more of trifluorotoluene, difluorobenzene, trifluorobenzene, toluene, ethylbenzene, decafluoropentane, perfluorohexanone, perfluorobutyl ethyl ether, and perfluorobutyl methyl ether.

[0008] Optionally, the mass fraction of the non-polar diluent in the electrolyte is 25%-50%.

[0009] Optionally, the mass ratio of the sulfur additive to the non-polar diluent is 1:100-1:25.

[0010] Optionally, the carbonate solvent is one or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate.

[0011] A second aspect of the present invention provides a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and the above-mentioned electrolyte.

[0012] Optionally, the positive electrode plate includes a positive electrode current collector and a positive electrode active material, wherein the positive electrode active material includes any one of lithium nickel manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminum oxide, or a combination of at least two of them.

[0013] Optionally, the negative electrode plate includes a negative electrode current collector and a negative electrode active material, wherein the negative electrode active material includes any one of soft carbon, hard carbon, artificial graphite, natural graphite, silicon, silicon oxides, silicon carbon compounds or lithium titanate, or a combination of at least two thereof.

[0014] The electrolyte provided in some examples of the present invention achieves stable compatibility between the electrolyte and positive electrode materials such as high-nickel ternary materials by using a non-polar diluent.

[0015] Specifically, on the one hand, since the non-polar diluent itself has good oxidation stability and is not prone to oxidative decomposition, the addition of the non-polar diluent in the electrolyte can reduce the contact between the carbonate solvent and the positive electrode surface, thereby reducing the probability of carbonate solvent decomposition; on the other hand, the non-polar diluent has no dissociative effect on lithium salts, so the addition of the non-polar diluent can compress the solvation structure of lithium ions in the electrolyte, forming a solvation structure containing anions, thereby improving the overall oxidation stability of the electrolyte. In addition, the addition of the diluent can also reduce the activity of the carbonate solvent, further improving the oxidation stability of the carbonate solvent.

[0016] However, non-polar diluents have the problem of poor reduction stability, and they will undergo continuous reduction decomposition on the surface of the negative electrode made of materials such as graphite or silicon. The inventors found that adding a sulfur-based additive represented by formula (1), (2) or (3) to the electrolyte containing the non-polar diluent can further solve this problem, achieve good compatibility between the non-polar diluent and the negative electrode, and will not affect the remaining performance of the lithium-ion battery. This is because the solid electrolyte interface (SEI) product generated by this type of sulfur-based additive at the negative electrode has a high polarity, and the solubility of this SEI film product in the non-polar diluent is extremely low, so a complete and dense SEI film can be formed. At the same time, the unsaturation and sulfur content of this type of sulfur-based additive are higher than those of commonly used sulfur-based additives (such as vinyl sulfate DTD and 1,3-propane sultone PS, etc.), so the SEI film components generated by its decomposition have a higher degree of cross-linking and more sulfur content, which further improves the compactness of the SEI film and reduces the solubility of the SEI film components in the non-polar diluent. The sulfur-based additive used in the present invention can not only prevent the reduction and decomposition of the non-polar diluent on the surface of the negative electrode, but also construct a high-quality SEI film with a very small addition amount. DETAILED DESCRIPTION

[0017] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0018] Unless otherwise specified or incompatible herewith, the terms and phrases used herein shall have the following meanings:

[0019] Solid Electrolyte Interface (SEI): During the charging and discharging process of lithium-ion batteries, the electrode material and the electrolyte react at the solid-liquid interface to form a passivation layer covering the surface of the electrode material.

[0020] Battery State of Charge (SOC): SOC is the percentage of the remaining battery power to the rated capacity of the battery, which is used to reflect the remaining capacity of the battery and the ability of the battery to continue working. When the battery is fully discharged, the SOC is 0, and when it is fully charged, the SOC is 1, which is generally expressed in 0-100%.

[0021] In this article, when it comes to numerical ranges, unless otherwise specified, the distribution of optional values ​​within the numerical range is considered continuous and includes the two numerical endpoints (i.e., the minimum value and the maximum value) of the numerical range, as well as every value between the two numerical endpoints. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be combined.

[0022] The first aspect of the present invention provides an electrolyte, comprising a solvent, a lithium salt, a non-polar diluent and a sulfur-based additive. The solvent comprises a carbonate solvent; the lithium salt is dissolved in the solvent; the mass fraction of the non-polar diluent in the electrolyte is 21%-60%; the mass ratio of the sulfur-based additive to the non-polar diluent is 1:200-1:10, and the sulfur-based additive is a compound represented by formula (1), (2) or (3).

[0023]

[0024] That is, the sulfur-based additive is one or more of [4,4'-bis(1,3,2-dioxothiolane)]2,2,2',2'-tetraoxide, glyoxal disulfate, and 1,3,6,8-tetraoxa-2,7-dithiaspiro[4.4]nonane 2,2,7,7-tetraoxide.

[0025] In the electrolyte of the lithium-ion battery, since carbonate solvents have a good dissociation degree for lithium salts and carbonate solvents have good compatibility with graphite negative electrodes. In an embodiment of the present invention, the solvent in the electrolyte includes a carbonate solvent, specifically one or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate.

[0026] However, carbonate solvents have poor oxidation stability. With the increase of nickel content in ternary cathode materials, conventional electrolytes based on carbonate solvents can no longer meet the requirements of electrochemical stability. Currently, the method of adding cathode film-forming additives to the electrolyte is often used to solve the problem of poor oxidation stability of the electrolyte, but this method usually leads to the deterioration of other electrical properties, such as power performance and low temperature performance.

[0027] Therefore, in some embodiments of the present invention, the electrolyte has a non-polar diluent component to improve the oxidation stability of the electrolyte and achieve stable compatibility between the electrolyte and positive electrode materials such as high-nickel ternary. On the one hand, since the non-polar diluent itself has good oxidation stability and is not prone to oxidative decomposition, the addition of the non-polar diluent can reduce the contact between the carbonate solvent and the positive electrode surface, thereby reducing the probability of oxidative decomposition of the carbonate solvent; on the other hand, the non-polar diluent has no dissociative effect on the lithium salt, so the addition of the non-polar diluent can compress the solvation structure of the lithium ions in the electrolyte, so that it forms a solvation structure containing anions, thereby improving the overall oxidation stability of the electrolyte. In addition, the addition of the non-polar diluent can also reduce the activity of the carbonate solvent, which can also improve the oxidation stability of the carbonate solvent. In some embodiments of the present invention, the non-polar diluent is preferably one or more of trifluorotoluene, difluorobenzene, trifluorobenzene, toluene, ethylbenzene, decafluoropentane, perfluorohexanone, perfluorobutyl ethyl ether, and perfluorobutyl methyl ether, and more preferably, the non-polar diluent is trifluorotoluene. In order to effectively improve the overall oxidation stability of the electrolyte and adjust the solvation structure while maintaining the stability of the conductivity of the electrolyte, the mass fraction of the non-polar diluent in the electrolyte is preferably 21%-60%, and more preferably, the mass fraction is 25%-50%.

[0028] By analyzing the test results of the lithium-ion battery cycle capacity of the embodiments of the present invention, the inventors found that due to the poor reduction stability of the non-polar diluent, it will undergo continuous reduction decomposition on the surface of the negative electrode such as graphite or silicon of the lithium-ion battery. In response to this problem, the inventors introduced a sulfur-based additive represented by formula (1), (2) or (3) into the electrolyte of some embodiments of the present invention, thereby achieving good compatibility between the non-polar diluent and the negative electrode and maintaining other properties of the lithium-ion battery in a good stable state. The structural formula of the above-mentioned sulfur-based additive is as follows:

[0029]

[0030] The reason why the sulfur-based additive with the above structural formula can achieve good compatibility between the non-polar diluent and the negative electrode in the embodiment of the present invention is that, on the one hand, the SEI film product generated by this type of sulfur-based additive at the negative electrode has a high polarity, and the solubility of this type of SEI film product in the non-polar diluent is extremely low, so it can form a complete and dense SEI film; on the other hand, the unsaturation and sulfur content of this type of sulfur-based additive are higher than those of commonly used sulfur-based additives (such as DTD and PS, etc.), so the SEI film components generated by its decomposition have a higher degree of cross-linking and more sulfur content, thereby further improving the compactness of the SEI film and reducing the solubility of the SEI film components in the non-polar diluent. This type of sulfur-based additive can not only prevent the reduction and decomposition of the diluent, but also build a high-quality SEI film with a very small addition amount.

[0031] Among them, in some embodiments of the present invention, the sulfur-based additive is preferably [4,4'-bis(1,3,2-dioxothiolane)]2,2,2',2'-tetraoxide, that is, formula (1). In order to achieve good compatibility between the non-polar diluent and the negative electrode and keep other properties of the lithium-ion battery in a stable state, in the embodiments of the present invention, the mass ratio of the sulfur-based additive represented by formula (1), (2) or (3) to the non-polar diluent is preferably 1:200-1:10, and more preferably, the mass ratio is 1:100-1:25.

[0032] In some other embodiments of the present invention, the electrolyte further includes a fluorinated additive and a lithium salt additive. The fluorinated additive can participate in the formation of the SEI film together with the sulfur-based additive represented by formula (1), (2) or (3) introduced in the embodiments of the present invention, forming an SEI film rich in inorganic components such as lithium fluoride and lithium sulfide. The above uniform and dense SEI film can ensure the stability of the cycle and high-temperature storage performance of the lithium-ion battery; and the lithium salt additive can introduce different anionic groups into the solvation structure of lithium ions. These anionic groups can participate in the film formation of the positive electrode CEI / negative electrode SEI, improve the film formation quality, and avoid the electrolyte from having continuous side reactions on the electrode surface and causing the loss of active lithium. The fluorinated additive is preferably one or more of fluoroethylene carbonate, tris (2,2,2-trifluoroethyl) phosphate, 2-fluoropyridine, and bis(2,2,2-trifluoroethyl) carbonate, and the mass fraction of the fluorinated additive in the electrolyte is preferably 1%-12%; the lithium salt additive is preferably one or more of lithium difluorooxalatoborate (LiDFOB), lithium difluorobis(oxalatophosphate) (LiODFP), lithium difluorophosphate (LiPO2F2), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium dioxalatoborate (LiBOB), and the mass fraction of the lithium salt additive in the electrolyte is preferably 0.1%-5%.

[0033] The second aspect of the present invention also provides a lithium-ion battery, which includes a positive electrode sheet, a negative electrode sheet, a separator and the electrolyte in the above embodiment. During the battery charging and discharging process, lithium ions are embedded and extracted back and forth between the positive electrode sheet and the negative electrode sheet, the separator is arranged between the positive electrode sheet and the negative electrode sheet to play a role of isolation, and the electrolyte plays a role of conducting ions between the positive electrode sheet and the negative electrode sheet.

[0034] The positive electrode plate of the lithium-ion battery provided in the embodiment of the present invention includes a positive electrode current collector and a positive electrode active material. The positive electrode current collector is usually made of a material with good electrical conductivity and mechanical strength, which is not limited here. In the embodiment of the present invention, aluminum foil is preferably used as the positive electrode current collector. The positive electrode active material may include any one of lithium nickel manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminum oxide, or a combination of at least two of them. In the lithium-ion battery provided in the embodiment of the present invention, the positive electrode active material is preferably lithium nickel cobalt manganese oxide with the chemical formula LiNi x Mn y Co z O2(x+y+z=1). Preferably, 0.6≤x<1, more preferably, the positive electrode active material is LiNi 0.9 Mn 0.05 Co 0.05 O2.

[0035] The negative electrode sheet of the lithium-ion battery includes a negative electrode current collector and a negative electrode active material. The negative electrode current collector can be made of a material with good conductivity and mechanical strength, which is not limited here. The present invention preferably uses copper foil as the negative electrode current collector. The negative electrode active material may include any one of soft carbon, hard carbon, artificial graphite, natural graphite, silicon, silicon oxide compounds, silicon carbon compounds, and lithium titanate, or a combination of at least two of them. Those skilled in the art can choose according to actual needs. In the embodiment of the present invention, the negative electrode active material of the lithium-ion battery is preferably graphite.

[0036] The isolation membrane is selected from conventional types in the art, for example, a polyethylene (PE) or polypropylene (PP) porous membrane can be selected as the isolation membrane, the thickness of the isolation membrane is 9 to 18 μm, the air permeability is 180 s / 100 mL to 380 s / 100 mL; the porosity is 30% to 50%.

[0037] The technical scheme of the present invention is described in detail below through specific examples and comparative examples. Unless otherwise specified, the raw materials and reagents used in the following examples are all commercially available products, or can be prepared by conventional methods in the art, and the instruments used in the examples are all commercially available.

[0038] The electrolyte compositions of different groups of embodiments and comparative examples are specifically referred to Table 1

[0039] Example 1

[0040] This embodiment provides a lithium-ion battery electrolyte, in which the solvent is composed of ethylene carbonate and ethyl methyl carbonate in a mass ratio of 1:9; the selected lithium salt is lithium hexafluorophosphate (LiPF6), and the concentration of the lithium salt is 1 mol / L; the selected non-polar diluent is trifluorotoluene, and its mass fraction in the electrolyte is 35%; the selected sulfur additive is [4,4'-bis(1,3,2-dioxothiolane)] 2,2,2',2'-tetraoxide, that is, formula (1), and its mass fraction in the electrolyte is 0.5%. In addition to the non-polar diluent, the sulfur additive, and the lithium salt, the rest of the electrolyte is the above-mentioned mixed solvent.

[0041] Embodiment 2-7

[0042] The system is the same as that in Example 1, but the mass fractions of trifluorotoluene in the electrolyte are 15%, 21%, 25%, 50%, 60% and 70% respectively, and the rest are the same as in Example 1.

[0043] Embodiment 8-13

[0044] The system is the same as that in Example 1, but the mass fractions of formula (1) in the electrolyte are 0.1%, 0.175%, 0.35%, 1.4%, 3.5% and 7% respectively, and the rest are the same as in Example 1.

[0045] Embodiment 14

[0046] The system is the same as that in Example 1, except that toluene is used as a non-polar diluent, and its mass fraction in the electrolyte is 35%. The rest is the same as that in Example 1.

[0047] Embodiment 15

[0048] The system is the same as that in Example 1, except that ethylbenzene is used as the non-polar diluent, and its mass fraction in the electrolyte is 35%. The rest is the same as that in Example 1.

[0049] Example 16

[0050] The system is the same as that in Example 1, except that decafluoropentane is used as a non-polar diluent, and its mass fraction in the electrolyte is 35%. The rest is the same as that in Example 1.

[0051] Embodiment 17

[0052] The system is the same as that in Example 1, except that perfluorohexanone is used as a non-polar diluent, and its mass fraction in the electrolyte is 35%. The rest is the same as that in Example 1.

[0053] Embodiment 18

[0054] The system is the same as that in Example 1, except that perfluorobutyl ether is used as a non-polar diluent, and its mass fraction in the electrolyte is 35%. The rest is the same as that in Example 1.

[0055] Embodiment 19

[0056] The system is the same as that of Example 1, except that glyoxal disulfate, i.e., formula (2), is used as a sulfur-based additive, and its mass fraction in the electrolyte is 0.5%. The rest is the same as that of Example 1.

[0057] Embodiment 20

[0058] The same as the system in Example 1, 1,3,6,8-tetraoxa-2,7-dithiaspiro[4.4]nonane 2,2,7,7-tetraoxide, i.e., formula (3), was used as the sulfur additive, and its mass fraction in the electrolyte was 0.5%. The rest was the same as in Example 1.

[0059] Embodiment 21

[0060] The same as the system in Example 1, using formula (1) and formula (2) as sulfur additives at the same time, the mass fractions of formula (1) and formula (2) in the electrolyte are 0.3% and 1% respectively, and the rest is the same as Example 1.

[0061] Embodiment 22

[0062] The same as the system in Example 1, using formula (2) and formula (3) as sulfur additives at the same time, the mass fractions of formula (2) and formula (3) in the electrolyte are 0.2% and 0.8% respectively, and the rest is the same as in Example 1.

[0063] Embodiment 23

[0064] The same as the system in Example 1, using formula (1) and formula (3) as sulfur additives at the same time, the mass fractions of formula (1) and formula (3) in the electrolyte are 0.5% and 0.3% respectively, and the rest is the same as in Example 1.

[0065] Comparative Example 1

[0066] The system is the same as that in Example 1, except that no non-polar diluent is used when preparing the electrolyte, and the rest is the same as that in Example 1.

[0067] Comparative Example 2

[0068] The system is the same as that in Example 1, except that no sulfur-based additive is used in preparing the electrolyte, and the rest is the same as that in Example 1.

[0069] Comparative Example 3

[0070] The system is the same as that in Example 1, except that no non-polar diluent and sulfur-based additive are used in preparing the electrolyte, and the rest is the same as that in Example 1.

[0071] Comparative Example 4

[0072] The same as the system in Example 1, no sulfur-based additive represented by formula (1), (2) or (3) is used in the preparation of the electrolyte, and 1,3-propane sultone (PS) is used as an additive, and its mass fraction in the electrolyte is 0.5%. The rest is the same as in Example 1.

[0073] Comparative Example 5

[0074] The same as the system in Example 1, no sulfur-based additive represented by formula (1), (2) or (3) is used in the preparation of the electrolyte, and vinyl sulfate (DTD) is used as an additive, and its mass fraction in the electrolyte is 0.5%. The rest is the same as in Example 1.

[0075] Table 1. Electrolyte compositions of different groups of examples and comparative examples

[0076]

[0077]

[0078] The electrolytes of Examples 1 to 23 and Comparative Examples 1 to 5 were respectively used in the preparation of lithium ion batteries.

[0079] In the embodiment of the present invention, the electrochemical device is a lithium ion battery, and the lithium ion battery is a primary lithium ion battery or a secondary lithium ion battery, comprising: a positive electrode sheet, a negative electrode sheet, a separator between the positive electrode and the negative electrode, and an electrolyte. The preparation method of the secondary lithium ion battery in the embodiment of the present invention is as follows:

[0080] (1) Preparation of positive electrode sheet

[0081] The positive electrode active material (LiNi 0.9 Mn 0.05 Co 0.05 O2), conductive agent acetylene black, and binder polyvinylidene fluoride are fully stirred and mixed in an N-methylpyrrolidone (NMP) solvent system in a mass ratio of 95:3:2 to obtain a positive electrode slurry, and the positive electrode slurry is evenly coated on an aluminum foil, and then the aluminum foil is dried and cold pressed to obtain a positive electrode sheet. The thickness of the single-sided active material of the positive electrode sheet after cold pressing is 50 μm.

[0082] (2) Preparation of negative electrode sheet

[0083] The negative electrode active material graphite, the conductive agent acetylene black, the binder styrene butadiene rubber, and the thickener sodium carbon methyl cellulose are fully stirred and mixed in a deionized water solvent system in a mass ratio of 96:2:1:1 to obtain a negative electrode slurry, and the negative electrode slurry is evenly coated on a copper foil, and then the copper foil is dried and cold pressed to obtain a negative electrode sheet.

[0084] (3) Preparation of diaphragm

[0085] Polyethylene (PE) was used as the separator.

[0086] (4) Preparation of electrolyte

[0087] In a glove box with an actual oxygen content of 0.1ppm, a moisture content of 0.1ppm and a nitrogen content of 99.999%, ethylene carbonate (EC) and ethyl methyl carbonate (EMC) are mixed in a mass ratio of 1:9 to form a solvent; the lithium salt in the electrolyte is lithium hexafluorophosphate (LiPF6) with a concentration of 1 mol / L; the types of non-polar diluents and additives selected in the electrolytes of Examples 1-23 and Comparative Examples 1-5 of the present invention and the mass fraction based on the total weight of the electrolyte are all based on the settings in Table 1 above, and the electrolyte contains the non-polar diluent, additives and lithium salt, and the rest is the solvent. The above ingredients are mixed to obtain an electrolyte. The electrolytes in different embodiments and comparative examples are prepared in the same manner except that the proportions of the ingredients are specified in the table.

[0088] (5) Preparation of secondary lithium-ion batteries

[0089] The positive electrode sheet, separator, and negative electrode sheet prepared above are stacked in order, so that the separator is located between the positive electrode sheet and the negative electrode sheet to play an isolating role, and a bare battery cell is obtained. The bare battery cell is loaded into an aluminum-plastic film, and then baked at 80°C to remove water, and then the corresponding electrolyte in Examples 1-23 and Comparative Examples 1-5 is injected and sealed, and then the finished soft-package lithium-ion secondary battery is obtained through the processes of standing, hot and cold pressing, formation, clamping, and capacity separation.

[0090] The performance of lithium-ion batteries assembled from the electrolytes in Examples 1-23 and Comparative Examples 1-5 was tested. The test results are shown in Tables 2, 3, 4, 5, and 6. The test methods are as follows:

[0091] (1) Capacity retention test of normal temperature cycle at 25°C

[0092] At 25°C, charge the battery at 1C constant current to 4.25V, then charge at 4.25V constant voltage until the current is less than 0.05C, leave it for 10 minutes, and then discharge it at 1C constant current to 2.5V. Test the discharge capacity of the battery at this time, which is the discharge capacity of the first cycle; the battery is cycled multiple times under the above conditions, and the capacity retention rate of the battery after 400 cycles is calculated. The capacity retention rate after the cycle is calculated according to the following formula:

[0093] Capacity retention rate (%) = (discharge capacity corresponding to 400 cycles / discharge capacity of the first cycle) × 100%.

[0094] (2) Volume expansion test after 30-day storage at 60°C

[0095] At 25°C, the battery was charged to 4.25V at 1C constant current, and then charged to 0.05C at constant voltage. The volume of the battery was tested using the water displacement method and recorded as V0. The fully charged battery was then placed in a 60°C oven for 30 days, and the volume after storage was tested using the water displacement method and recorded as V1. The volume expansion rate of the battery before storage was calculated using the following formula:

[0096] Volume expansion ratio (%) = (V1-V0) / V0×100%.

[0097] The test results are shown in Tables 2, 3, 4, 5, and 6.

[0098] Table 2. Lithium-ion battery performance test results of Example 1 and Examples 2-7

[0099]

[0100] Table 3. Lithium ion battery performance test results of Example 1 and Examples 8-13

[0101]

[0102] Table 4. Lithium ion battery performance test results of Example 1 and Examples 14-18

[0103]

[0104] Table 5. Lithium ion battery performance test results of Example 1 and Examples 19-23

[0105]

[0106] Table 6. Lithium ion battery performance test results of Example 1 and Comparative Examples 1-5

[0107]

[0108]

[0109] Analyzing the above data, we can draw the following conclusions:

[0110] Comparing the data in Table 2, it can be seen that when the mass fraction of the non-polar diluent in the electrolyte is 15%-70%, within this mass fraction range, if the non-polar diluent content is too low, it is not possible to effectively improve the overall oxidation stability of the electrolyte, nor to adjust the solvation structure, resulting in the carbonate solvent continuing to oxidize and decompose; if the content is too high, since the diluent itself cannot dissolve the lithium salt, it will cause the lithium salt dissociation degree to decrease, resulting in a significant decrease in the electrolyte conductivity, and the battery cannot perform as it should. The mass fraction of the non-polar diluent in the electrolyte is preferably 21%-60%, and more preferably, the mass fraction is 25%-50%.

[0111] Comparing the data in Table 3, it can be seen that when the mass ratio of the sulfur additive having the structure of formula (1) to the non-polar diluent in the electrolyte is 1:350-1:5, within this mass ratio range, if the content of the sulfur additive having the structure of formula (1) is too low, it is insufficient to form a complete SEI film at the negative electrode, thereby causing the problem of reduction and decomposition of the non-polar diluent at the negative electrode to be unsolved; if its content is too high, it will significantly increase the viscosity of the electrolyte, affecting the transmission of lithium ions in the electrolyte, thereby causing a significant increase in the battery impedance, making it difficult for the battery to exert its proper electrical performance. The mass ratio is preferably 1:200-1:10, and more preferably 1:100-1:25.

[0112] By comparing the data in Tables 4 and 6, it can be seen that the introduction of a non-polar diluent into the electrolyte can greatly improve the oxidative stability of the electrolyte and achieve stable compatibility between the electrolyte and the high-nickel ternary positive electrode. The lithium-ion battery composed of the electrolyte can exhibit relatively stable and good cycle performance and can delay the attenuation of the cycle life of the lithium-ion battery. Among them, the non-polar diluent is preferably trifluorotoluene and perfluorobutyl ether, and more preferably, the non-polar diluent is trifluorotoluene.

[0113] Comparing the data in Tables 5 and 6, it can be seen that the introduction of a sulfur-based additive having one or more combinations of formulas (1), (2), and (3) into the electrolyte can solve the problem that the non-polar diluent has poor reduction stability, thereby continuously reducing and decomposing on the surface of the negative electrode such as graphite or silicon; at the same time, the unsaturation degree and sulfur content of the sulfur-based additive having one or more combinations of formulas (1), (2), and (3) are higher than those of the commonly used sulfur-based additives (such as DTD and PS, etc.), so the SEI film component generated by its decomposition has a higher cross-linking degree and more sulfur content, thereby further improving the compactness of the SEI film and reducing the solubility of the SEI film component in the non-polar diluent, and finally achieving good compatibility between the non-polar diluent and the negative electrode and maintaining the stability of the remaining performance of the lithium-ion battery. Among them, the sulfur-based additive is preferably a compound represented by formula (1), or a combination of the compounds represented by formula (1) and formula (3), and more preferably, the sulfur-based additive is preferably a compound represented by formula (1).

[0114] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An electrolyte, characterized in that: include: A solvent, wherein the solvent comprises a carbonate solvent; a lithium salt, dissolved in the solvent; A non-polar diluent, wherein the mass fraction of the non-polar diluent in the electrolyte is 21%-60%; A sulfur-based additive, wherein the mass ratio of the sulfur-based additive to the non-polar diluent is 1:200-1:10, and the sulfur-based additive is a compound represented by formula (1), (2) or (3):

2. The electrolyte according to claim 1, characterized in that The non-polar diluent is one or more of trifluorotoluene, difluorobenzene, trifluorobenzene, toluene, ethylbenzene, decafluoropentane, perfluorohexanone, perfluorobutyl ethyl ether, and perfluorobutyl methyl ether.

3. The electrolyte according to claim 1 or 2, characterized in that The mass fraction of the non-polar diluent in the electrolyte is 25%-50%.

4. The electrolyte according to claim 1, characterized in that The mass ratio of the sulfur-based additive to the non-polar diluent is 1:100-1:

25.

5. The electrolyte according to claim 1, characterized in that The carbonate solvent is one or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate.

6. A lithium ion battery, characterized in that: The lithium-ion battery comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte according to any one of claims 1 to 5.

7. The lithium ion battery according to claim 6, characterized in that The positive electrode plate includes a positive electrode current collector and a positive electrode active material, and the positive electrode active material includes any one of lithium nickel manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminum oxide, or a combination of at least two thereof.

8. The lithium ion battery according to claim 6, characterized in that The negative electrode plate includes a negative electrode current collector and a negative electrode active material, and the negative electrode active material includes any one of soft carbon, hard carbon, artificial graphite, natural graphite, silicon, silicon oxide, silicon carbon compound or lithium titanate, or a combination of at least two thereof.

Citation Information

Patent Citations

  • Lithium ion battery

    CN114122491A

  • Lithium ion battery

    CN114639872A

  • Secondary battery, battery module, battery pack, and electric device

    CN115692842A

  • Electrolyte and lithium ion secondary battery

    CN118572196A

Cited By

  • Non-aqueous electrolyte and lithium ion battery

    CN121215907A

  • Non-aqueous electrolyte and lithium ion battery

    CN121215907B